Big Data in traumatic brain injury; promise and challenges - Denes V Agoston; Dianne Langford (Concussion)
Traumatic brain injury (TBI) is a spectrum disease of overwhelming complexity, the research of which generates enormous amounts of structured, semi-structured and unstructured data. This resulting ...